The Improvement of Mathematical Communication Ability and Students’ Attitude Through Student Team Heroic Leadership Teaching-Learning Model - Rahayu Kariadinata; R. Poppy Yaniawati; Iyon Maryono; Abdul Rahman Sidik Maryono (Jurnal Analisa, 2026)
Mathematical communication ability is essential for students to solve mathematical problems effectively. However, empirical evidence suggests this competency remains underdeveloped in many Indonesian schools, necessitating innovative instructional interventions. This study examines the effectiveness of two cooperative learning models—Student Team Heroic Leadership with panel discussion (STHL-A) and Student Team Heroic Leadership with shopping windows (STHL-B)—compared to conventional instruction in enhancing students' mathematical communication skills. Conducted at SMP Negeri 2 Selaawi, Garut, West Java, the research employed a non-equivalent control group design with purposive sampling. Data were collected through pretests, posttests, and Likert-scale attitude questionnaires. The findings reveal three key outcomes. First, no significant difference was observed in the improvement of mathematical communication ability among the STHL-A, STHL-B, and conventional groups. Second, a significant difference was found in the final achievement of mathematical communication ability, with both STHL models outperforming the conventional approach. Third, students exhibited positive attitudes toward both STHL-A and STHL-B models. These results suggest that while all three models produced comparable gains in skill improvement, the STHL models were more effective in achieving higher final competency levels. Moreover, the positive student responses indicate that the STHL models are instructionally effective and well-received. Therefore, both STHL-A and STHL-B are recommended as viable alternatives to conventional teaching for fostering mathematical communication in junior high school settings.